Study on Optimizing Novel Antimicrobial Peptides with Bifunctional Activity to Prevent and Treat Peri-Implant Disease - Shuipeng Yu; Qian Zhang; Meilin Hu; Borui Zhao; Zhiyang Liu; Changyi Li; Xi Zhang (MDPI AG, 2022)
The bacterial invasions and inflammatory responses after implant placement often affect osseointegration; the increased secretion of pro-inflammatory cytokines can lead to poor formation of bone and bone absorption. Previous research has shown that the antimicrobial peptide 6K-F17 has antibacterial and immunomodulatory properties. The objective of this study was to optimize KR−1 and KR−2, based on 6K-F17, to apply to the tissue around the oral implant. Our first objective is to study its antibacterial properties, and then we intend to further study its osteogenic ability to osteoblasts by modulating the immune response of macrophages. In this research, KR−1 and KR−2 can inhibit the formation of bacterial biofilm, and further kill bacteria S. gordonii and F. nucleatum by destroying the cell wall and cell membrane of bacteria. The novel peptides restrained the activation of the NF-κB signaling pathway by reducing the phosphorylation levels of IκBα and p65, inhibiting the degradation of IκBα and the nuclear translocation of p65, and increasing the percentage of M2 phenotype in macrophages. This suppressed the inflammatory response induced by lipopolysaccharides and enhanced the osteogenic activity of osteoblasts; this, in turn, promoted osteogenesis. The antimicrobial peptide KR−1 showed better performance. Our results demonstrate that KR−1 and KR−2 have antibacterial and bone immunomodulatory effects, and further promote osteogenesis by modulating the immune microenvironment, which provides the possibility for the adjuvant treatment of peri-implant diseases.